v.17 - "Keynes, John Maynard" (New Delhi, 2013)
Between 1921 and 1923 Keynes was involved, with varying degrees of success, in a variety of attempts at influencing British and overseas opinion. This volume prints all the principal articles, letters and memoranda surrounding the publication of The Economic Consequences of the Peace, A Revision of the Treaty and the series 'Reconstruction in Europe', which he edited for the Manchester Guardian Commercial. It also includes important memoranda, articles and correspondence on Britain's post-war monetary policy and international financial policy. As such, it is an important companion to his published work of the period and an important source for material on his development as a monetary economist.
Keywords: Keynesianism